Pengembangan Aplikasi Mobile Pelaporan Keluhan Pelanggan PDAM Menggunakan Fitur Geotagging Berbasis Android (Studi Kasus: PDAM Tirta Tuah Benua Kutai Timur) - Anggi Mahadika Purnomo; Bayu Priyambadha; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
PDAM Tirta Tuah Benua East Kutai as regional owned enterprises that manages clean water in North Sangatta seeks to maximizing service and handling customer complaints quickly and precisely to realize the PDAM's mission. Based on interviews with PDAM, it can be concluded that the existing manually reporting procedure is considered ineffective because there are still various problem such as a lack of information about the part that handles customer. In addition, customers are also required to come directly to submit the payment invoices for bill complaints that are not according to usage. Another problem is about the location of the customers that given manually wich will make PDAM's employee feels difficult to find the address if the location is in a remote area. To handle the problems above, the solution that the author offers is to develop a mobile customer complaint reporting application where customers can report their complaints through a mobile application and employees can give a feedback through the admin's website. The author used waterfall model to developing the software. In this research using the geotagging feature to add location to the images sent by the customers. Then do the unit, validation, and compatibility testing. Based on the validation testing, it shows that all functions are valid, which means they are in accordance with the the defined requirements. And the result of compatibility testing show that mobile applications can be used on 4 different Android OS versions.